Ikhtiar Gereja Dalam Mewujudkan Misi Allah Bagi Umat Manusia Berdasarkan Matius 28:19-20 - Ronald Sianipar; Elisya Nita Anugrahni; Dwianjani E Nainggolan; Besti Niat Harefa; Srianti Hutabarat; Frans Erikson (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
Mission is the Great Commission that must be carried out by the church with true enthusiasm and sincerity. However, this part is sometimes not realized consistently within the church due to various problems and obstacles that occur in church institutions. Therefore, it is very important that the mission be carried out properly and spread to all existing groups. Thus, the aim of this article is to provide important points that must be carried out by the church in realizing God's mission in the world so that the church can grow and be consistent in carrying out the mission or Great Commission that has been commanded in Matthew 28:19-20. The method used in this paper is a descriptive qualitative method with an approach to library data sourced from books, Bibles, journals and other online media, then analyzing these sources and drawing conclusions. The result of this article is that the church has important points as an effort to overcome various challenges or problems in mission activities so that the church can maximize the realization of the great commission contained in Matthew 28:19-20 and the church grows healthily and consistently to carry out its responsibility, namely spreading good news for everyone.